DIFERENTIATED LEARNING FOR ELEMENTARY SCHOOL STUDENTS WITH NEURODEVELOPMENTAL DISORDERS: A SYSTEMATIC LITERATURE REVIEW - Rosyidah, Irma; Afidah, Febrian Nafisa Nurul; Mukhoiyaroh, Mukhoiyaroh (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study examines differentiated learning for elementary school students with neurodevelopmental disorders, such as ADHD, autism spectrum disorder (ASD), and dyslexia. The study emphasizes the importance of adaptive and inclusive learning approaches to address diverse student needs. This research employed a Systematic Literature Review (SLR) method using the PRISMA 2020 framework. Data were collected using the Harzing Publish or Perish (PoP) application from Scopus, Google Scholar, Crossref, and Elicit, with inclusion criteria limited to Scopus- or SINTA-indexed articles published between 2020 and 2025. Of the 158 identified articles, four met all eligibility criteria and were analyzed using NVivo to identify key themes. The findings indicate that differentiated learning improves academic achievement, learning engagement, and students’ socio-emotional development by adjusting content, processes, products, and learning environments. The review also highlights the importance of teacher readiness, interdisciplinary collaboration, and inclusive school support in optimizing learning outcomes and inclusive educational practices in elementary schools.